Integrated Analysis of the miRNAome and Transcriptome Reveals miRNA–mRNA Regulatory Networks in Catharanthus roseus Through Cuscuta campestris-Mediated Infection With “Candidatus Liberibacter asiaticus” - Zeng, Chunhua; Wu, Haodi; Cao, Mengji; Zhou, Changyong; Wang, Xuefeng; Fu, Shimin (Frontiers in Microbiology, 2022)
Citrus Huanglongbing (HLB) is the most devastating disease of citrus caused by the Gram-negative phloem-limited bacterium ‘Candidatus Liberibacter asiaticus’ (CLas). It can be transmitted by the Asian citrus psyllid ‘Diaphorina citri’, by grafting, and by the holoparasitic dodder. In this study, the non-natural host periwinkle (Catharanthus roseus) was infected via dodder (Cuscuta campestris) from CLas-infected citrus plants, and the asymptomatic leaves (AS) were subjected to transcriptomic and small-RNA profiling. The results were analyzed together with a transcriptome dataset from the NCBI repository that included leaves for which symptoms had just occurred (S) and yellowing leaves (Y). There were 3675 differentially expressed genes (DEGs) identified in AS, and 6390 more DEGs in S and further 2109 DEGs in Y. These DEGs were commonly enriched in photosystem, chloroplast, membrane, oxidation-reduction process, metal/zinc ion binding on GO. A total of 14974 DEGs and 336 DE miRNAs (30 conserved and 301 novel) were identified. Through weighted gene co-expression network and nested network analyses, two critical nested miRNA–mRNA regulatory networks were identified with four conserved miRNAs. The primary miR164-NAC1 network is potentially involved in plant defense responses against CLas from the early infection stage to symptom development. The secondary network revealed the regulation of secondary metabolism and nutrient homeostasis through miR828-MYB94/miR1134-HSF4 and miR827-ATG8 regulatory networks, respectively. The findings discovered new potential mechanisms in periwinkle-CLas interactions, and its confirmation can be done in citrus-CLas system later on. The advantages of periwinkle plants in facilitating the quick establishment and greater multiplication of CLas, and shortening latency for disease symptom development make it a great surrogate for further studies, which could expedite our understanding of CLas pathogenesis.